2018
DOI: 10.1007/s00216-018-1198-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of total dinutuximab concentrations in neuroblastoma patients with liquid chromatography tandem mass spectrometry

Abstract: Neuroblastoma is one of the most commonly found solid tumors in children. The monoclonal antibody dinutuximab (DNX) targets the sialic acid-containing glycosphingolipid GD2 expressed on almost all neuroblastoma tumor cells and induces cell lysis. However, the expression of GD2 is not limited to tumor cells only, but is also present on central nerve tissue and peripheral nerve cells explaining dinutuximab toxicity. The most common adverse reactions are pain and discomfort, which may lead to discontinuation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This closely parallels the dinutuximab serum levels drawn in a single pediatric patient, with the highest level measured on the third day of a four-day cycle. 18 Despite availability of PCA hydromorphone bolus doses through the entire four-day course of the dinutuximab infusion, pain persisted between cycles and our patient continued to require methadone and as needed oxycodone with acetaminophen in the outpatient setting despite being opioid naive. Pain control improved during cycle 3 as her baseline opioid needs from the first two cycles provided guidance, though the patient reported that the pain was still extremely difficult to tolerate.…”
Section: Discussionmentioning
confidence: 77%
“…This closely parallels the dinutuximab serum levels drawn in a single pediatric patient, with the highest level measured on the third day of a four-day cycle. 18 Despite availability of PCA hydromorphone bolus doses through the entire four-day course of the dinutuximab infusion, pain persisted between cycles and our patient continued to require methadone and as needed oxycodone with acetaminophen in the outpatient setting despite being opioid naive. Pain control improved during cycle 3 as her baseline opioid needs from the first two cycles provided guidance, though the patient reported that the pain was still extremely difficult to tolerate.…”
Section: Discussionmentioning
confidence: 77%
“…An ammonium sulfate (AS) protein precipitation method was chosen for simplicity and fast workflow. 29 From the plasma sample, 10 μl was taken and diluted with a 5‐μl IS solution and 85 μL of Tris buffer (50 mM, pH 8, 0.5% OG) in a 1‐ml LoBind 96 deep‐well plate and mixed for 1 minute at 1350 rpm. Then, 100 μL of saturated AS solution was added to each sample and mixed for 1 minute at room temperature at 1350 rpm to precipitate both therapeutic and endogenous immunoglobulins from the plasma samples.…”
Section: Methodsmentioning
confidence: 99%
“…In 2010, sipuleucel-T became the first therapeutic cancer vaccine to receive FDA approval for the treatment of metastatic hormone-refractory prostate cancer [ 89 ]. In 2015, dinutuximab (marketed as unituxin) was granted orphan drug designation and approved by the FDA and EMA to be used as part of a first-line treatment on paediatric patients with high-risk neuroblastoma [ 90 , 91 ]. Subsequently, dinutuximab β (marketed as isquette), used as a second-line treatment of neuroblastoma, was also approved in 2017 [ 92 ].…”
Section: Challenges Of Anti-id Antibodies As Vaccinesmentioning
confidence: 99%